Dialektika Progresif; “One Dimensional Man”, Desublimasi Represif: Kritik Herbert Marcuse Atas Masyarakat Industri Modern - Sumarni, Lilik; Seran , Alexander (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
Marcuse’s main idea is that technology and mass consumption have created a social order that makes people "one-dimensional human," losing the ability to think critically and see social alternatives. Marcuse argued that a fundamental change in society was needed to allow the liberation of individuals from the pressures and constraints generated by the capitalist system. The purpose of this paper is to critically explore the dialectic of Herbert Marcuse's approach to the "one-dimensional man" and repressive desublimation. This research method uses a qualitative approach with a critical approach to the study of Herbert Marcuse's thought. The concepts of "repressive sublimation" and "administrated" describe the way modern society directs its natural human impulses into a form regulated and controlled by social and political authorities. Repressive sublimation results in the suppression of self-expression and creativity, while administrated refers to the dominance of bureaucracy and technocracy in managing society. This results in unfreedom and homogenization in society. This study contains Marcuse's biography, looking at the content of his works, contributions to knowledge and communication, and the relevance of Herbert Marcuse's critical thinking to the current context. One Dimensional Man; is used as a spectacular work a narrative created to criticize the irrational and oppressive grand narrative of capitalism with an exploitative power structure through the affirmative dimension, for which Marcuse suggests rebuilding the dimension of negation; Where society again has critical power and is no longer in a state of silence.